Inequalities in energy drink consumption among UK adolescents: a mixed-methods study. Issue 3 (6th March 2023) - Vogel, Christina; Shaw, Sarah; Strömmer, Sofia; Crozier, Sarah; Jenner, Sarah; Cooper, Cyrus; Baird, Janis; Inskip, Hazel; Barker, Mary
Abstract: Objective: To examine energy drink consumption among adolescents in the UK and associations with deprivation and dietary inequalities. Design: Quantitative dietary and demographic data from the National Diet and Nutrition Survey (NDNS) repeated cross-sectional survey were analysed using logistic regression models. Qualitative data from semi-structured interviews were analysed using inductive thematic analysis. Setting: UK. Participants: Quantitative data: nationally representative sample of 2587 adolescents aged 11–18 years. Qualitative data: 20 parents, 9 teachers and 28 adolescents from Hampshire, UK. Results: NDNS data showed adolescents' consumption of energy drinks was associated with poorer dietary quality (OR 0·46 per sd ; 95 % CI (0·37, 0·58); P < 0·001). Adolescents from more deprived areas and lower income households were more likely to consume energy drinks than those in more affluent areas and households (OR 1·40; 95 % CI (1·16, 1·69); P < 0·001; OR 0·98 per £1000; 95 % CI (0·96, 0·99); P < 0·001, respectively). Between 2008 and 2016, energy drink consumption among adolescents living in the most deprived areas increased, but decreased among those living in the most affluent neighbourhoods ( P = 0·04). Qualitative data identified three themes. First, many adolescents drink energy drinks because of their friends and because the unbranded drinks are cheap. Second, energy drink consumption clusters with other unhealthy eating behaviours and adolescents do not know why energy drinks are unhealthy. Third, adolescents believe voluntary bans in retail outlets and schools do not work. Conclusions: This study supports the introduction of age-dependent legal restrictions on the sale of energy drinks which may help curb existing socio-economic disparities in adolescents' energy drink intake.